2018
DOI: 10.1016/j.ijrobp.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy as an Alternative to Transarterial Chemoembolization for Hepatocellular Carcinoma

Abstract: Stereotactic body radiation therapy is a safe alternative to TACE for 1 to 2 tumors and provides better LC, with no observed difference in OS. Prospective comparative trials of TACE and SBRT are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(98 citation statements)
references
References 39 publications
(34 reference statements)
3
90
0
5
Order By: Relevance
“…SBRT does not seem to compromise the measured survival outcomes after TACE. Sapir et al (23) also reported that 209 patients with 287 HCC tumors, and 28 of these cases with portal vein branch thrombosis (BCLC-C), were treated with TACE (n = 84) or SBRT (n = 125) in western countries, where hepatitis C virus (70%) and alcohol abuse (20%) were the main cause of HCC. It was also found that SBRT can be an alternative to TACE for local HCC with one to two tumors and provided better LC, with no difference in OS.…”
Section: Discussionmentioning
confidence: 99%
“…SBRT does not seem to compromise the measured survival outcomes after TACE. Sapir et al (23) also reported that 209 patients with 287 HCC tumors, and 28 of these cases with portal vein branch thrombosis (BCLC-C), were treated with TACE (n = 84) or SBRT (n = 125) in western countries, where hepatitis C virus (70%) and alcohol abuse (20%) were the main cause of HCC. It was also found that SBRT can be an alternative to TACE for local HCC with one to two tumors and provided better LC, with no difference in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, at the University of Michigan, where SBRT may be offered for salvage after TACE/RFA failure or as the remaining liver-directed therapy for patients ineligible for other locoregional control options, SBRT for one to two HCC tumors was associated with local control rates of 97% at 1 year and 91% at 2 years. 62 In contrast, patients receiving TACE for one to two HCC tumors had local control rates of 47% at 1 year and 23% at 2 years. This was despite treatment bias favoring TACE for patients who were transplant candidates and thus had fewer liver-directed treatments.…”
Section: Locally Advanced Unresectable Hccmentioning
confidence: 96%
“…[58][59][60] In contrast, grade 3 or higher toxicities from SBRT to unresectable HCC range from 6 to 27%. 43,44,54,62,63 Notably, despite the lower reported rates of grade 3 or higher toxicity, bowel ulceration is a serious and potentially life-threatening complication of SBRT. Therefore, we stress that treatment at a center with experience in SBRT is of utmost importance.…”
Section: Locally Advanced Unresectable Hccmentioning
confidence: 99%
“…The authors concluded that SBRT is a safe alternative to TACE for 1 to 2 tumors. 10 In a multinational retrospective study, investigators used propensity score matching to compare radiofrequency ablation (RFA) (N ÂŒ 1,607) with one of the largest cohorts of SBRT (N ÂŒ 497). SBRT tumors were often larger (median 2.8 vs. 1.8 cm, p < 0.001) and were more likely to have received prior liver-directed therapy (2 vs. 0 time, p < 0.001).…”
Section: General Approach To Sbrt For Hccmentioning
confidence: 99%